Migration and Urbanity in Rural Areas. Developments in the German-Luxembourg Border Region - Boesen, Elisabeth; Schnuer, Gregor; Wille, Christian (Geographien der Grenzen. Räume - Ordnungen - Verflechtungen, 2020)
Abstract: „Studies on the connection between migration and urbanity are usually concerned with conditions and developments in cities. The presence of ‘urbanity’ in rural space is the topic of the present contribution. It will be discussed using the example of residential migration in the Greater Region SaarLorLux. The massive influx of residential migrants from Luxembourg into the border regions of the neighbouring countries is a relatively recent phenomenon, the main cause of which lies in the developments in the real-estate market in the Grand Duchy of Luxembourg. This phenomenon is of special interest for the topic of migration in rural areas in two regards: because of the important demographic changes produced by the residential migrants in individual border villages and because of the complex composition of the group of residential migrants, which is extremely differentiated regarding the dimension rural—urban. Central to the article is the question, whether urban attitudes and practices become visible in German border villages, and, if so, how the migratory movement from Luxembourg influences this ‘rural urbanity’. Furthermore, taking the everyday practices of the residential migrants as starting point, it asks in how far the dichotomy urbanity—rurality presents a conceptual approach for the examination of individual and structural integration processes.“
Keywords: Ländliche Entwicklung; Ländlicher Raum; Migration; Stadt

Cross-Border Metropolitan Integration in Europe. The Case of Luxembourg, Basel, and Geneva. - Sohn, Christophe; Reitel, Bernard; Walther, Olivier (Environment and Planning C. Politics and Space, 2009)
Abstract: „In this paper we question the integration processes in three small cross-border metropolitan areas: Luxembourg, Basel, and Geneva. By referring to an original analysis framework, we evaluate the nature and intensity of the functional and institutional integration and highlight the elements that structure the cooperation between the actors. The analysis shows that there is not necessarily a reciprocal link between the size of the functional area and the extent of the cooperation. Whilst no metropolitan-sized organisation is on the agenda in Luxembourg, the example of Basel and Geneva shows that the presence of a national border offers an opportunity to invent original forms of governance, to increase the autonomy of the local authorities by different types of cooperation which transcend the institutional and territorial divides, and to promote the international character of the metropolitan centre. In a context of global competition, these features represent an undeniable benefit.“
Keywords: Basel; Genf; Schweiz; Soziale Integration; Stadt

Métropolisation et intégration transfrontalière. Le paradoxe luxembourgeois - Sohn, Christophe; Walther, Olivier (Espaces et sociétés, 2009)
Abstract: „À partir de l’exemple de Luxembourg, cet article traite de l’intégration des espaces frontaliers métropolitains, en s’interrogeant sur l’articulation de leurs propriétés institutionnelles et fonctionnelles. Dans un premier temps, il questionne l’évolution fonctionnelle de l’aire métropolitaine en prenant pour variable l’intensité des flux pendulaires, l’objectif étant de montrer l’existence d’un espace métropolitain aux dimensions transfrontalières. Dans un second temps, l’article examine les initiatives entreprises dans le domaine de l’intégration institutionnelle par les acteurs politiques. Le cas luxembourgeois permet alors de montrer que, contrairement à d’autres métropoles européennes et de manière paradoxale, il n’existe aujourd’hui aucune gouvernance métropolitaine transfrontalière susceptible de répondre aux enjeux de l’aire fonctionnelle préalablement définie. Cette situation singulière résulte du rôle prépondérant de l’État luxembourgeois – plutôt que de la Ville – dans les dynamiques métropolitaines.“
Keywords: Soziale Integration; Stadt